A Hemicyanine‐Assembled Upconversion Nanosystem for NIR‐Excited Visualization of Carbon Monoxide Bio‐Signaling In Vivo. Issue 28 (17th June 2022) - Ye, Minan; Zhang, Jie; Jiang, Detao; Tan, Qi; Li, Jingyun; Yao, Cheng; Zhu, Chenjie; Zhou, Yi
Abstract: Carbon monoxide (CO) is considered as the second gasotransmitter involved in a series of physiological and pathological processes. Although a number of organic fluorescent probes have been developed for imaging CO, these probes display excitation within the ultraviolet or visible range, which restrict their applications in the complex biosystems. In the present work, a strategy is developed to construct an upconversion nanoparticles‐based nanosystem for upconversion luminescent (UCL) sensing CO. This nanosystem exhibits a fast response to CO with high sensitivity and selectivity in aqueous solution by a near‐infrared‐excited ratiometric UCL detection method. Meanwhile, laser scanning upconversion luminescence microscope experiments demonstrate that this nanosystem can visualize the endogenous CO bio‐signaling in living cells, deep tissues, zebrafish, and living mice by ratiometric UCL imaging. In particular, this nanosystem has been successfully employed in visualization of the endogenous CO bio‐signaling through up‐regulation of heme oxygenase‐1 (HO‐1) in the progression of hypoxia, acute inflammation, or ischemic injury. This work demonstrates that the outstanding performance of the nanosystem not only can provide an effective tool for further understanding the role of CO in the physiological and pathological environment, but also may have great potential ability for tracking the expression of HO‐1 in living systems. Abstract : Ratiometric upconversion luminescent visualization of endogenous CO in vitro and in vivo: a strategy is developed using mesoporous silica‐modified upconversion nanophosphor assembled with CyD1 and PdCl2  as an additive to form a nanosystem, which not only can trace fluctuations in CO levels, but also may have great potential ability for evaluating the expression of heme oxygenase‐1 in different models.